Role of Exchange Rate and Exchange Rate Risk for Exporters of Manufacturing Goods in Light of the IBRKK Surveys - Marczewski, Krzysztof (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
Objective: To conduct an analysis of the determinants of the impact of the exchange rate level and its volatility on the exporter’s decisions regarding the size of exports and scale and forms of their hedging against exchange rate risk.Research Design & Methods: The analysis is based on the results of surveys of Polish exporters from the manufacturing industry carried out at the Institute of Market, Consumption and Business Cycles Research in 2007–2016. These results are considered in the context of theoretical findings from a simple microeconomic optimization model.Findings: The analysis of survey results shows that almost half of Polish exporters remain sensitive to exchange rate movements, while not, at the same time, hedging their foreign currency exposure either on the forward market or by means of natural hedging. The other half of exporters protect themselves mainly with natural methods. Due to the observed heterogeneity of the exporters population, econometric studies generally do not show exchange rate fluctuations to have a significant effect on exports.Implications / Recommendations: The low demand for hedging is related both to the structural features of enterprises (small-sized firms or firms with a low share of export in sales), but also to the relatively high export profitability experienced by most firms in recent years. Among  companies who hedge, a significant shore use various forms of contractual natural hedging, exploiting for this purpose, as a hedging shield, import inputs, settlements of exports in PLN or payments for domestic purchases of materials settled in a foreign currency.Contribution: Referring to results of multi-year surveys, the article shows the complexity of the determinants impacting the exchange rate and its volatility on reactions of Polish exporters of manufacturing goods.